Trends in jail admissions rates - Gido, Rosemary L. (American journal of criminal justice, 1989)
Historical data on national and state jail admissions trends have not been fully explored for theoretical and empirical insights into what causes jail populations to vary over time. This study draws on New York State historical jail records, research on national and state imprisonment trends, and “macro” perspectives on crime control and punishment. The analysis explores some of the possible causal relationships between variation in jail admissions and unemployment, major demographic trends, war, depression, jail capacity, and law enforcement and judicial practices. Theoretical, methodological, and operational implications of the research are discussed.